2004
DOI: 10.1161/01.cir.0000136813.89036.21
|View full text |Cite
|
Sign up to set email alerts
|

CD34 + and Endothelial Progenitor Cells in Patients With Various Degrees of Congestive Heart Failure

Abstract: Background-Peripheral blood CD34ϩ cells and circulating endothelial progenitor cells (EPCs) increase in myocardial infarction and vascular injuries as a reflection of endothelial damage. Despite the occurrence of endothelial dysfunction in heart failure (HF), no data are available on EPC mobilization in this setting. We investigated the pattern of CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
253
2
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(281 citation statements)
references
References 16 publications
16
253
2
8
Order By: Relevance
“…55 EPC (CD133 ϩ /Flk-1 ϩ ) was also reported to be inversely related to the severity of congestive heart failure. 55,56 Reduced number of EPCs was also seen in cardiac transplantation patients with vasculopathy 57 and in patients with in-stent restenosis. 58 In contrast, elevated EPC levels were reported in patients with unstable angina 59 and in patients with acute myocardial infarction 60 in association with elevation in plasma C-reactive protein levels.…”
Section: Epc and Cardiovascular Diseasesmentioning
confidence: 91%
“…55 EPC (CD133 ϩ /Flk-1 ϩ ) was also reported to be inversely related to the severity of congestive heart failure. 55,56 Reduced number of EPCs was also seen in cardiac transplantation patients with vasculopathy 57 and in patients with in-stent restenosis. 58 In contrast, elevated EPC levels were reported in patients with unstable angina 59 and in patients with acute myocardial infarction 60 in association with elevation in plasma C-reactive protein levels.…”
Section: Epc and Cardiovascular Diseasesmentioning
confidence: 91%
“…Statistical analysis revealed that not only was CFU-EC concentration altered, but that the CFU-EC concentration reflected vascular health, since brachial artery reactivity increased with increasing CFU-EC concentration. Later studies demonstrated that the concentration of CFU-ECs was decreased in patients with type I diabetes, 48 chronic obstructive pulmonary disease, 49 congestive heart failure, 50 and rheumatoid arthritis. 51 However, some studies have contradicted the trend of lower numbers in disease susceptibility; CFU-EC concentration has been shown to be significantly increased in patients with unstable angina, 52 at the time of myocardial infarction (MI), 53 and within 7 days of an acute MI.…”
Section: Spotlightmentioning
confidence: 99%
“…8,9 Recently, advanced stages of heart failure were shown to be associated with reduced levels of cEPCs. 10 One study showed ICM was associated with selective impairment of progenitor cell function in the bone marrow and in the peripheral blood. 11 Endothelial cells can release microparticles after inflammatory stimulation, and the presence of increased levels of circulating endothelial-derived microparticles (cEMPs) has been documented in various pathologic conditions including coronary syndromes, in which they reflect endothelial dysfunction and are associated with a poor clinical outcome.…”
Section: Introductionmentioning
confidence: 99%